Enhanced photovoltaic performance of inverted polymer solar cells utilizing versatile chemically functionalized ZnO@graphene quantum dot monolayer - Moon, Byung Joon; Lee, Kyu Seung; Shim, Jaeho; Park, Soohyung; Kim, Se Ho; Bae, Sukang; Park, Min; Lee, Chang-Lyoul; Choi, Won Kook; Yi, Yeonjin; Hwang, Jun Yeon; Son, Dong Ick (ELSEVIER, 2016)
Recently, interfacial engineering approaches as an efficient strategy for improving the power conversion efficiencies (PCEs) of inverted polymer solar cells (iPSCs) has attracted considerable attention. Among various efficient solutions, solution-processed metal-oxide films prepared from metal oxide sol-gel precursors (or nanoparticles) and polymer surface modifiers are typically used as electron selective interfaces in the inverted cell geometry. To present a more effective strategy for surpassing the limitations of traditional methods, such as an unintended increase in series or contact resistance by incompatibility at the organic/inorganic interface, inherently insulating nature of non-conjugated surface modifiers and oxygen adsorption (or photo-induced doping) of metal-oxide layer, we synthesize chemically surface-modified ZnO@graphene core-shell type quantum dots (ZGQDs) with well-characterization of the chemical, optical and electrical properties, and fabricate iPSCs consisting of ITO/PEIE/ZGQD-OAs/photoactive layer/MoO3/Ag. The mono-layered QDs play the multi-functional role as surface modifier, sub-photosensitizer and electron transport layer. Using this effective approach, we achieve the highest conversion efficiency of similar to 10.3% resulting from improved interfacial properties and efficient charge transfer based on static quenching and charge transfer reaction from ZnO to graphene nanosheets (with drastically reduced tau(avg) (similar to 60 ps)), which is verified by various analysis tools. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: HIGHLY EFFICIENT; OXIDE; INTERFACE; STABILITY; DEGRADATION; LAYER; ACID